Do we need a strategic high technology policy? The case for a federal government high technology policy - Konrad Seitz (Intereconomics, 1992)
Germany, with the rest of Western Europe, is in danger of losing the race to Japan for the lead in the field of the new key technologies. What is the reason for this? Do we need a strategic high technology policy? The following three articles present differing answers to these questions.
Keywords: 330; Industrial Policy